2019
DOI: 10.1128/msphere.00700-18
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Sequencing Uncovers Survival Mechanisms of Salmonella enterica Serovar Enteritidis in Antibacterial Egg White

Abstract: Salmonella enterica serovar Enteritidis is a major foodborne pathogen that causes salmonellosis mainly through contaminated chicken eggs or egg products and has been a worldwide public health threat since 1980. Frequent outbreaks of this serotype through eggs correlate significantly with its exceptional survival ability in the antibacterial egg white. Research on the survival mechanism of S. Enteritidis in egg white will help to further understand the complex and highly effective antibacterial mechanisms of eg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
46
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(51 citation statements)
references
References 89 publications
(132 reference statements)
5
46
0
Order By: Relevance
“…Through gene deletion and complementary, we demonstrated that seven differently expressed genes (including gene yoaE) obtained from our published transcriptome data contributed to the survivability of S. Enteritidis in egg white (17). Six of them (except gene yoaE) were included in our previous published paper (17).…”
mentioning
confidence: 82%
See 3 more Smart Citations
“…Through gene deletion and complementary, we demonstrated that seven differently expressed genes (including gene yoaE) obtained from our published transcriptome data contributed to the survivability of S. Enteritidis in egg white (17). Six of them (except gene yoaE) were included in our previous published paper (17).…”
mentioning
confidence: 82%
“…Through gene deletion and complementary, we demonstrated that seven differently expressed genes (including gene yoaE) obtained from our published transcriptome data contributed to the survivability of S. Enteritidis in egg white (17). Six of them (except gene yoaE) were included in our previous published paper (17). In this study, gene yoaE (A7J12_06270), which encodes a predicted inner membrane protein and was upregulated by 15-to 18-fold at the mRNA level in egg white (17), was further characterized.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…For example, the effects of cranberry extract and antimicrobial proteins on the growth rates and transcriptomics of S. typhimurium were investigated. The expressions of related genes, such as those involved in iron acquisition, flagella, energy metabolism, pathogenicity, virulence islands and the cell membrane, were significantly downregulated after bacteriostatic treatment in S. typhimurium [22,23]. According to Song et al and Wang et al [24,25], the transcriptome was used to explore the mechanism of antibacterial activity of BITC on Vibrio parahaemolyticus and Staphylococcus aureus.…”
Section: Introductionmentioning
confidence: 99%